Scouting Education as a Forum for Discipline Formation - Fitriani, Ayuk (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Discipline is the initial foundation of character building, the purpose of this study describes scouting education activities in supporting the discipline character education of fourth grade students of SD Negeri 4 Jrakah. This research includes Qualitative Descriptive Research, which is research that produces descriptive data in the form of written or spoken words from people who are observed or interviewed. 20 fourth grade students as research subjects. Data collection techniques used in this research through in-depth interviews, observation and documentation. To ensure data validity, source triangulation was used. In analyzing the data, this research uses descriptive analysis techniques interactive model. Based on the data collected, then described, categorized and analyzed, to be able to draw conclusions. From various scouting activities (rigging, morse & semaphore, coding, first aid in accidents, yells, songs & claps, marching, mapping, camping and ceremonies) are able to form students in carrying out disciplinary activities. Scouting education can be used as a medium to train the discipline of fourth grade students of SD Negeri 4 Jrakah.